2-(3-Methoxyphenoxy)pyrimidine - Nasir, S.B.; Abdullah, Z.; Fairuz, Z.A.; Ng, S.W.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
In the title compound, C(11)H(10)N(2)O(2), the benzene ring faces towards one of the pyrimidine N atoms, and is almost orthogonal to the plane through the pyrimidine ring [dihedral angle = 84.40 (14)degrees]. In the crystal, the presence of C-H...pi and pi-pi [centroid-centroid separation = 3.7658 (18) A] interactions leads to a supramolecular array in the ac plane. The layers thus formed interdigitate along the b axis.